2020
DOI: 10.1073/pnas.2012096117
|View full text |Cite
|
Sign up to set email alerts
|

Sociopolitical stress and acute cardiovascular disease hospitalizations around the 2016 presidential election

Abstract: Previous research suggests that stressors may trigger the onset of acute cardiovascular disease (CVD) events within hours to days, but there has been limited research around sociopolitical events such as presidential elections. Among adults ≥18 y of age in Kaiser Permanente Southern California, hospitalization rates for acute CVD were compared in the time period immediately prior to and following the 2016 presidential election date. Hospitalization for CVD was defined as an inpatient or emergency department di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Robust evidence for societal events acting as widespread stressors comes from large cross-sectional samples where data were being collected prior to and after focal events (4,(18)(19)(20). Yet, the necessary reliance on natural experiment designs has led to key limitations in the extant literature.…”
mentioning
confidence: 99%
“…Robust evidence for societal events acting as widespread stressors comes from large cross-sectional samples where data were being collected prior to and after focal events (4,(18)(19)(20). Yet, the necessary reliance on natural experiment designs has led to key limitations in the extant literature.…”
mentioning
confidence: 99%
“…In our prior study, 6 we used a 2-day risk window based on existing literature of other types of psychosocial events. In the current study we chose a longer window a priori because the final result was not known for 5 days after the date of the 2020 election, and to account for the protracted nature of associated stress and eventual announcement of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study of Kaiser Permanente Southern California (KPSC) members, we found a 62% higher risk of hospitalization for acute myocardial infarction (AMI) or stroke in the 2 days immediately following the 2016 presidential election compared with the same 2 days in the 1 and 2 weeks prior. 6 Other studies have similarly presented evidence of cardiovascular and noncardiovascular adverse outcomes associated with political stress and, more specifically, the 2016 presidential election. 7 , 8 , 9 The aim of the current study was to replicate and expand on findings from our prior study of the 2016 presidential election that was limited to the Southern California population by examining hospitalizations for acute CVD around the 2020 presidential election among adults in KPSC and Kaiser Permanente Northern California (KPNC), 2 large integrated health care delivery systems that provide comprehensive care for more than 9 million persons.…”
Section: Introductionmentioning
confidence: 96%
“…(1) To identify the effect of psychological/mental stress to cause cardiac arrhythmia (2) To identify the relation between psychological stress and ventricular arrhythmia.…”
Section: Objectivesmentioning
confidence: 99%
“…The result of this clinical study was positive. A direct connection between mental stress and cardiac problems has been identified [2]. Chronic psychosocial stressors can cause aggravation of Coronary Artery Atherosclerosis, as well as Temporary Endothelial Dysfunction, and then can even lead to cellular necrosis, at last, organ degeneration.…”
Section: Introductionmentioning
confidence: 99%